Impact of Study Abroad Experiences on the Multilingual Development of Chinese Students: A Case Study in Thailand - Rattanaphumma, Ratchaporn; Visuttakul, Chidchamai (Journal of Research and Curriculum Development, 2022)
The 21st century is the age of internationalization and globalization, and the increased effort put into emphasizing local and global opportunities is relatively obvious. This paper presents both quantitative and qualitative research examining study abroad experiences in Thailand impacted the intercultural communicative competence of students, eventually leading to multilingual development of their Thai language ability, English language proficiency, and intercultural abilities, which were the three main constructs for data collection. The population consisted of 30 purposively selected Chinese students enrolled in a graduate program in the 2020 academic year at private universities in Thailand. After a minimum stay of one year in Thailand, the students were asked to complete a questionnaire with a five-point Likert scale to self-assess their Thai language ability, English language proficiency, and intercultural abilities. The results demonstrated that study abroad experiences provided students with both positive linguistic and cultural outcomes. The overall mean scores of English language proficiency and intercultural abilities were at a high level, which indicated a high level of development of the students in English and intercultural abilities, whereas their Thai language abilities were at a low level. The interview findings also corroborated the findings of the questionnaire. The study revealed that study abroad experiences offered ample opportunities to pathways to bilingualism and multilingualism. Therefore, investment in the international experiences of students to meet the demands of global competence should be essential to gradually move both students and institutions towards internationalization and globalization.